MANAJEMEN KELAS RESPONSIF GENDER - Susilawati Susilawati (Cross-border, 2019)
Class management is very important for the implementation of good management. The study of this research is qualitative in which the results show that to develop gender responsive education management includes the following: (a) the provision of access to quality education, especially basic education equally for boys and girls, both through schooling and external education. school; (b) providing equal access to education for adults who are unable to attend school education; (c) increasing the provision of literacy education services for the adult population, especially women; (d) increasing coordination, information and education in order to prioritize gender-based education; and (e) institutional development of educational institutions both at the central and regional levels regarding gender-based education.